PENGARUH KARAKTERISTIK PEKERJAAN, PEMBERDAYAAN DAN MOTIVASI TERHADAP KINERJA OPERATOR SD NEGERI DI JAKARTA TIMUR - HAMDANI, DEDE (PPs UNJ, 2015)
The purpose of this study was to determine the effect job characteristic model, empowerment and motivation of job performance state elementary school operator in east jakarta. this research tried to answer problems about job characteristic model with evidence increasing of service operator school. the research was conducted on job performance state elementary school operator in east jakarta involving of 238 state elementary school operator had been selected from the target populations of 588 state elementary school operator by using quantitative approach with path analysis methods. the research of hypothesis testing show; (1) job characteristic model had a direct effect positif on job performance, (2) empowerment had a direct effect positif on job performance, (3) motivation had a direct effect positif on job performance, (4) job characteristic had a direct effect positif on motivation, (5) empowerment had a direct effect positif on motivation, therefore to improve the job perfromance state elementary school operator in east jakarta, need to increase job charactersitic model, empowerment and motivation.